A survey of patients with laryngotracheal stenosis on future clinical trial design. (April 2022) - Lina, Ioan; Berges, Alexandra; Ospino, Rafael; Motz, Kevin; Davis, Ruth; Anderson, Catherine; Stroud, Mary; Rodweller, Casey; Gelbard, Alexander; Hillel, Alexander T
Background/Aims: Laryngotracheal stenosis is a rare but devastating proximal airway fibrosis that restricts a patient's ability to breathe. Treatment is primarily surgical and to date, there has never been a multi-institutional, randomized, prospective, and interventional clinical trial for a medical therapy to treat laryngotracheal stenosis. Therefore, we aimed to obtain patient feedback to guide successful trial design, recruitment, retention, and for identifying potential barriers to study participation. Methods: Over 1000 members of an international laryngotracheal stenosis online support community (the Living with Idiopathic Subglottic Stenosis Facebook group) were sent two questionnaires for a proposed interventional double-blinded, randomized, placebo-controlled clinical trial. Results: A total of 317 and 558 participants responded to the first and second surveys, respectively. The majority of participants (77%) were willing to consider enrollment, regardless of having a 50% chance of receiving placebo versus treatment (78%). The majority (84%) of participants were willing to travel 200 miles to participate for up to six in-person visits over 50 days. Specific side effects, including anemia/thrombocytopenia (72%) or risk of infection (69.3%) had the greatest impact on clinical trial participation with other side effects (peripheral edema (53%), oral ulcers (51%), and gastrointestinal side effects (41%)) having less impact. Conclusion: Patients with laryngotracheal stenosis possess nuanced insight into their disease and treatment options. As a group, they are extremely motivated for better therapies. Future laryngotracheal stenosis clinical trials should focus on providing excellent side effect -related education and utilizing feedback from online advocacy groups to optimize recruitment and retention.